2020
DOI: 10.3389/fneur.2020.580184
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Conducted oVEMP Latency Delays Assist in the Differential Diagnosis of Large Air-Conducted oVEMP Amplitudes

Abstract: Conclusions: A two-step protocol of click AC oVEMP amplitudes and 125 Hz BC oVEMP latency measures optimizes the specificity of VEMP testing in SCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Several studies have shown that symptomatic patients with near dehiscence have audiometric and vestibular testing results similar to normal non-dehiscent ears and significantly different from ears with frank dehiscence, suggesting that near dehiscence does not have the same effect on inner ear biomechanics (three studies with a total of 223 SCDS ears, 90 near dehiscence syndrome ears and 83 normal ears; only one study assessed SCDS ears vs. normal ears) ( 65 , 94 , 153 ). By contrast, there are reports of patients with near dehiscence demonstrating supranormal bone conduction thresholds, reduced cVEMP thresholds and increased oVEMP amplitudes, suggesting that these findings may be inconsistent in this patient population (11 and 86 ears) ( 152 , 154 ). ECochG has also been shown to be produce an increased SP to AP ratio among patients with near dehiscence ( 153 ).…”
Section: Challenges In Scds Managementmentioning
confidence: 77%
“…Several studies have shown that symptomatic patients with near dehiscence have audiometric and vestibular testing results similar to normal non-dehiscent ears and significantly different from ears with frank dehiscence, suggesting that near dehiscence does not have the same effect on inner ear biomechanics (three studies with a total of 223 SCDS ears, 90 near dehiscence syndrome ears and 83 normal ears; only one study assessed SCDS ears vs. normal ears) ( 65 , 94 , 153 ). By contrast, there are reports of patients with near dehiscence demonstrating supranormal bone conduction thresholds, reduced cVEMP thresholds and increased oVEMP amplitudes, suggesting that these findings may be inconsistent in this patient population (11 and 86 ears) ( 152 , 154 ). ECochG has also been shown to be produce an increased SP to AP ratio among patients with near dehiscence ( 153 ).…”
Section: Challenges In Scds Managementmentioning
confidence: 77%
“…A possible contribution of the horizontal canal through the spread of regional mobilization of endolymphatic fluid has also been suggested in animals by Carey et al [41]. The implication of an asymmetric concomitant stimulation of otolith structures in SCD patients is otherwise corroborated in the clinical setting by abnormal otolithic test results (ipsilateral hyperexcitability of cVEMPs and oVEMPs) not only with sounds (air-conducted stimulations) but also after bone-conducted vibration stimulations [14,15,38,42].…”
Section: Characteristics Of the Nystagmus Obtained In Scd (Direction ...mentioning
confidence: 87%
“…Otolith tests (oVEMP, cVEMP) are currently described as the most efficient in SCD diagnosis; they are positive in 80-90% of cases with ACS stimulations [11,14] but also after BC stimulations [42].…”
Section: Svin As a Bone-conducted Tullio Phenomenon (Bctp)mentioning
confidence: 99%
“…After excluding 607 duplicate articles, 408 articles were excluded due to the lack of a relevant of title and abstract. The full text of the remaining 27 articles was evaluated, and 18 studies were excluded due to the inclusion of other interventions or a lack of outcomes (1,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Consequently, nine studies with 721 participants were finally included in the metaanalysis.…”
Section: Study Selectionmentioning
confidence: 99%